Mind and Cosmos. Why the Materialist Neo-Darwinian Conception of Nature is Almost Certainly False - Franz Magnis-Suseno (P3TK, Sanata Dharma University, 2020)
Mind and Cosmos. Why the Materialist Neo-Darwinian Conception of Nature is Almost Certainly False